Prices in Buenos Aires during a cycle of war and political instability, 1825-1835 (Quinto Sol, 2019)
This paper analyzes the evolution of the inflation of the prices of goods that occurred in Buenos Aires after the war between the United Provinces of the Rio de la Plata and Brazil, and of political crisis during the period between 1825 and 1835. The article explores and analyzes in general and in particular the different and ongoing changes in the prices of imported goods, exports and local consumption during a critical cycle of the economy of the Río de la Plata.
Keywords: prices; war; economy